Magellanic Woodpeckers as Indicators of Wood-Dwelling Beetle Diversity in Trees with Different Levels of Decay and Under Changing Environmental Conditions - Vergara-Egert, P; Quiroz-Espinoza, M; Alaniz-Baeza, A; Zuñiga-Alvarez, A; Hidalgo-Corrotea, C (John Wiley and Sons Inc, 2025)
Although woodpeckers are considered ecological indicators, their relationships with wood-dwelling beetle communities are scarcely known. Woodpeckers and wood-dwelling beetles respond to wood decay and forest disturbances; however, it is unclear how these effects propagate through saproxylic networks. We investigated whether the trees used by Magellanic woodpeckers (Campephilus magellanicus) have a greater diversity of wood-dwelling beetles of different functional groups. We also examined the direct and indirect effects of environmental conditions and wood decay on beetles and woodpeckers. We sampled beetles using emergence traps and characterised wood decay using tomography, comparing stem sections excavated by woodpeckers with those of control trees. The abundance and taxonomic richness of beetles belonging to different guilds (predators, wood borers and mycophages) was higher in sections where woodpeckers foraged. However, these factors were also influenced by remote sensing environmental variables and their interactions with woodpeckers. Wood borers positively influenced beetles of other guilds (predators and mycophages). Climatic conditions, vegetation structure, and biophysical properties had direct effects on wood decay and indirect effects on woodpeckers and wood-dwelling beetles via decay. Wood decay had positive direct and indirect effects on predators, mycophages and woodpeckers, but not on wood borers. These results suggest Magellanic woodpeckers can serve as indicators of wood-dwelling beetle communities. Forest degradation and climate change have the potential to exert bottom-up control over interactions among woodpeckers and functional groups of wood-dwelling beetles. © 2025 Royal Entomological Society.